A comparison of the biogeographical and geomorphological characteristics of gullied and non-gullied valley head mires in eastern Lesotho - Deschamps, Christine L. (My University, 2008)
Environmental degradation is a serious problem in Lesotho, Africa. The majority of studies dealing with soil loss and gully erosion have mainly focused on the mechanics of the erosion. However, mountain watersheds are sensitive and vulnerable to degradation and in so being, have large inherent environmental implications. Gully erosion diversifies the micro-topographical and hydrological environment. The severe changes and eventual system degradation incurred as a result of gullying has rarely been quantified. This paper specifically highlights mire phytogeographic responses to valley head degradation at selected sites in eastern Lesotho by comparing patterns observed in gullied mires to those seen in other non-gullied mires. Soil and vegetation belt transects are set up across five mires (2 gullied) in the highlands of eastern Lesotho. The response of many of the plant species to the overall environmental gradient was asymmetrical and unimodal in pattern. The spatial distribution of the soil’s physical properties, topography and vegetation community patterns were found to reflect the spatial mosaic of the soil moisture gradient. The negative impact that gullying has on the ecohydrological regime of the valley heads is evident and is allowing for shrub encroachment. Both the wetland and dryland vegetation communities correlate strongly with the changes in the surface soil moisture gradient. Gully erosion is clearly a threshold phenomenon. Continued grassland degradation, accelerated soil erosion and subsequent gullying of the wetlands will lead to plant and animal diversity loss, decreased livestock productivity, sediment-laden water and shortened dam life-span.
Keywords: wetland; Lesotho; alpine; gully erosion; South Africa; FEN; BOG